2022
DOI: 10.3390/jcm11071911
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Wound (UAW) Debridement in the Treatment of Diabetic Foot Ulcer: A Systematic Review and Meta-Analysis

Abstract: A systematic review and meta-analysis were carried out to investigate the effect of ultrasound-assisted wound (UAW) debridement in patients with diabetic foot ulcers (DFUs). All selected studies were evaluated using the Cochrane risk of bias tool to assess the risk of bias for randomized controlled trials. PubMed and Web of Science were searched in October 2021 to find randomized clinical trials (RCT) assessing the effect of UAW debridement on DFUs. RevMan v5.4. was used to analyze the data with the Mantel–Hae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Larger, more homogeneous samples are obligatory for this investigation. This was also emphasised in previous studies that employed a linked meta‐analysis technique and found comparable consequences of the effect 39‐41 …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Larger, more homogeneous samples are obligatory for this investigation. This was also emphasised in previous studies that employed a linked meta‐analysis technique and found comparable consequences of the effect 39‐41 …”
Section: Discussionmentioning
confidence: 69%
“…This was also emphasised in previous studies that employed a linked meta-analysis technique and found comparable consequences of the effect. [39][40][41] Well-led RCTs are necessary to weigh these features as well as the blend of diverse ethnicities, gender, ages, and other parameters of subjects as the meta-analysis could not define whether differences in them are linked to the wound healing rate. In conclusion, the USSD applied to DFUs caused a significantly higher wound healing rate compared with the standard care and the placebo.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested also in a previous similar meta‐analyses study which showed similar promising outcomes for low‐frequency ultrasound in improving the non‐healed chronic wound ulcers at ≥3 months and reducing the percentage of chronic wound ulcers area reduction. 34 , 45 , 46 , 47 , 48 , 49 Well‐conducted randomised controlled trials are needed to assess these factors and the combination of different gender, ages, ethnicity, and other variants of subjects; because our meta‐analysis study could not answer whether different ages and ethnicity are related to the results.…”
Section: Discussionmentioning
confidence: 99%
“…Eight randomized controlled trials (RCTs) met their inclusion criteria in patients with diabetic foot ulcers (DFUs). 12 Ultrasound-assisted wound debridement showed higher healing rates than placebo.…”
Section: Mechanicalmentioning
confidence: 97%
“…A recent systematic review and meta-analysis by Flores-Escobar and colleagues 12 investigated ultrasound-assisted wound debridement in comparison with a placebo. Eight randomized controlled trials (RCTs) met their inclusion criteria in patients with diabetic foot ulcers (DFUs) 12 . Ultrasound-assisted wound debridement showed higher healing rates than placebo.…”
Section: Choice Of Debridement Modalitymentioning
confidence: 99%